THE ATTITUDE OF OPEN PHILOSOPHY ON THE IDEA OF THE DEATH OF THE ELDERS OF THOUGHT AT ANDRE GLUCKS MAN - khouder, riad (Journal of Social Sciences and Humanities, 2020)
Dans cet article ,j’ai parlé de l’attitude de la nouvelle philosophie française dirigée par Gluksman , de la philosophie des ainés de la pensée marx et Platon , qu’il a rejetée , ainsi que de la critique de cette philosophie par Fethi Triki qui cosidérait cette philosophie comme ancienne et circonstancielle , et il a également donné à l’alternative une philosophie ouverte . Fathi Triki voit cette philosophie aussi veille que Marx , tout en étant descriptive et en produisant une vision raciste , Triki a également donné l'alternative pour contrer cette pensée fanatique . Cette philosophie excluait également toute morale et toute éducation , Gluksman du point de vue de Triki n'est pas une nouveauté en particulier lors de ses critiques de Platon , mais la plus part de ses critiques des philosophies Anglaises au service des juifs de France , et il a utilisé les moyens de propagande médiatique pour atteindre son objectif . - Summary : In this article , I discussed the attitude of the new philosophy in France ,the idea of the elders of thought and the reason for its rejection by Glucsman as well as the critique of this philosophy by Fathi Triki ,who sees this philosophy as old as Marx , as well as being descriptive and producting a racist view . Triki also gave the alternative to counter this fanatical thought and representative the open philosophy . Fathi Triki beleve that the new philosophy in France led by Gluksman was aimed at the first is to defame abuse and violence and all authoritarian practices , but in fact it is otherwise , its criticism of Marx and Plato is based only on the political sid without other areas , it also excluded all moral and educational , wich relied on many phylosophies and was the cause of the act liberation and spread of awareness with in the comunities , but Glucsman from view point of Triki did not come new especially during his criticism of Plato , but most of his criticism of the english philosophies to serve the jeuis of France . Glucsman also used the means of medea propaganda to achieve his goal , but in fact his clain is false because Plato 's philosophy did not call at all to the attachment , violence and autoritaritism but is a philosophy of humanity and liberation. The open philosophy according to Triki , is the halves of Plato because his ideas of diversity reject all closed thought based on racism , especially those that were brought by Gluksman , but stressed that plato's philosophy based on struggle . He also criticized Karl Marx and said that his political thought was based on autoritarianism and violence that caused the wars but in fact he did not see the intellectual life of Marx wich is otherwise , but calls for freedom. In order to restore the dignity of man and warking classes , but the most important thing about the criticism of Gluksman elders thought it is not true is alie because the fight against violence , according toTriki is not limited to one state without another and why does not talk Gluksman about the violence of jeuis against Palastinians and the stress of Africans in europe what violence he has in other countries and this is unacceptable .